The influence of supply chain networks, flexibility and integration on the performance of small and medium enterprise in the Southern Gauteng region - Omoruyi, Osayuwamen (My University, 2015)
The South Africa economy has embraced the importance of small and medium enterprises (SMEs) as agents of economic growth and sustainability. However, for SMEs to be more efficient and effective towards the growth of the economy, it is important for SMEs to implement and take cognisance of the global competitive strategy among the so-called “best in class” organisations in order to also sustain and grow their business. The supply chain network with its flexibility has become the most commonly used business strategy worldwide for the improvement of performance in organisations, more especially among larger organisations. In today’s competitive environment, successful organisations are those that have been able to link their business functions within the organisation itself as well as across other businesses outside the organisation. Competitive challenges in the modern business environment have resulted in the need for organisation to integrate business processes strategically across other business units within the supply chain network. Network perspective theory, social network theory, network management theory and relational view theory are discussed to better understand the importance of SMEs supply chain network, flexibility and integration. The purpose of this study was to examine the influence of supply chain network, flexibility and integration on the SMEs business performance in the Southern Gauteng region. The research survey was conducted in the Meyerton, Vereeniging and Vanderbijlpark and 401 SMEs participated in the study. SPSS 22.0 was used to analyse the data and AMOS 22.0 was used to perform the confirmatory factor analysis. The structural equation modelling (SEM) was used to assess the proposed model fit and to test the statistically significant relationship of the hypothesis. The research study results revealed that supply chain network, flexibility and integration positively influence SMEs business performance. This study contributes new knowledge to the existing literature by providing a research framework that can enhance SMEs performance and also provide practical recommendations based on the research findings for SMEs and for future research. Furthermore, as one of the first studies addressing the influence of supply chain network, flexibility and integration on the performance of SMEs in the southern Gauteng region it has generated new insights and information as well as outlined the strategic reasons for SME owners and managers to improve on their business relationships.
D. Tech. (Business, Logistics, Faculty of Management Sciences), Vaal University of Technology
Keywords: Small and medium enterprises; Supply chain network; 658.5; Physical distribution of goods; Business logistics